Changes in birth prevalence of hypoplastic left heart syndrome over the past half-century in Sweden. (3rd October 2022) - Giang Kok, W; Mandalenakis, Z; Fedchenko, M; Eriksson, P; Rosengren, A; Norman, M; Hanseus, K; Dellborg, M
Abstract: Background: Over the past decades improvements in surgical treatment and medical management have resulted in increased survival of children with congenital heart disease, where the most complex congenital heart diseases are now also suitable for treatment. Trends in live birth prevalence in one of the most complex congenital cardiac defects, hypoplastic left heart syndrome (HLHS) have not been reported. Purpose: The aim of this study was to assess trends in live-birth prevalence of patients with hypoplastic left heart syndrome over the past 50 years in Sweden. Method: The Swedish National Patient and Cause of Death register were linked to estimate the annual rates of HLHS among live-born infants from 1970 to 2017. Information on number of livebirths per year in 1970–2017 was obtained from Statistics Sweden. Results: A total of 838 infants with HLHS were identified during 1970–2017. The annual number of live born patients varied from 8 to 40 cases with a prevalence of 5.4 to 14.5 cases per 100, 000 live births in the 1970s, increasing to a peak of 33.9 cases per 100, 000 in 1993 and then decreasing from the late 1990s to reach an average level of 11.2 cases per 100, 000 live births in the period 2014–2017. Conclusion: The live-birth prevalence for HLHS increased to nearly six times of that in the 1970s during the 1990s. However, a subsequent decline was observed. This evolution most likely reflects a combination of increased tendency in recording the diagnosis as improved treatment becomes available and a decline related to antenatal diagnosis and termination of pregnancies. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Swedish state under an agreement between the Swedish government and county councils (the ALF agreement, grant numbers: 236611 and 917361), the Swedish Heart-Lung Foundation (grant number: 20180644).